If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 + x = 2 + 5x + 5 Reorder the terms: 3 + 6x + x = 2 + 5x + 5 Combine like terms: 6x + x = 7x 3 + 7x = 2 + 5x + 5 Reorder the terms: 3 + 7x = 2 + 5 + 5x Combine like terms: 2 + 5 = 7 3 + 7x = 7 + 5x Solving 3 + 7x = 7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 3 + 7x + -5x = 7 + 5x + -5x Combine like terms: 7x + -5x = 2x 3 + 2x = 7 + 5x + -5x Combine like terms: 5x + -5x = 0 3 + 2x = 7 + 0 3 + 2x = 7 Add '-3' to each side of the equation. 3 + -3 + 2x = 7 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 7 + -3 2x = 7 + -3 Combine like terms: 7 + -3 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| 0.20t^2-45.0t+1000=0 | | 0.20t^2-45.0t=1000 | | 9+10s-4=9s+47-6s | | -16t^2+3t+1.3=0 | | -7(x+1)-13=26+3 | | -32+28=4 | | y/15+6=y/6+12 | | -9=-6+3x | | 16x^4=y^2 | | 0=2(3x-5)+8(4x+7) | | -16t^2+3t+1.3=h(t) | | 12+m/4=3d-1/2 | | (2x-3)(x+3)=3 | | 4(a+3)=6(a-(5-a)) | | 6(3+v)+36v=13v | | 7r-8r=6 | | 5xy-3y-4=0 | | X-3/5+3/5=-x/2 | | -5t-26=18t | | -(100/-4) | | 3x+9=15forx | | 0=16t^2+44t-24 | | -3/4+7/3 | | 4=2a+37 | | 4x^2=12x-8 | | -4x^2-40x-106=0 | | -17=1+4n-7n | | g(x)=2f(x) | | -4/3-1 | | 6y+4=3(2y-10) | | 4/3-1 | | 2b-7b=5 |